Quality of granular seeds collected in commercial establishments in the State of Santa Catarina, Brazil - Cavalcante, Ricardo Miotto; Cavalcante, Jerffeson Araujo; Meneghello, Géri Eduardo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Grain production plays an important role in Brazilian agriculture. The main crops produced are soybeans and corn, followed by rice, beans and wheat. The State of Santa Catarina is responsible for much of the grain production in the southern region of the country. In this context, the use of quality seed ensures a better establishment of the crop and, consequently, greater productivity. Seed production and commercialization are determined by Law, guaranteeing the quality and identity of the seeds, dividing them into categories (Certified C1 and C2), and outside the certification system (S1 and S2). In addition to the categories, there are minimum criteria for the marketing of seeds such as: physical purity, germination, number of seeds of other cultivated species, number of wild seeds, number of noxious seeds tolerated and prohibited. In order to guarantee the established minimum standards, there is the external quality control system (CEQ), carried out by government agencies, in the seed lots of commercial establishments. Santa Catarina exercises the CEQ of the seeds commercialized through the Integrated Company of Agricultural Development of Santa Catarina (CIDASC). The objective of this study was to evaluate the physical and physiological quality of soybean, corn, rice, wheat and bean seeds collected from commercial establishments in the state of Santa Catarina during the period from 2013 to 2015. A total of 62 soybean seeds, 13 rice samples, 23 maize samples, 18 wheat samples and 20 bean seed samples were collected and submitted to the Official Laboratory (LANAGRO) for analysis, the physical purity, germination and determination of other seeds by number. The seed lots collected during the period are within the limits established in the legal standards, specific for each species, for the quality criteria evaluated.